Olaparib As Therapy For Metastatic-Castration Resistant Prostate Cancer : Systematic Review And Meta Analysis - Putra Gunawan, I Made Rian; Herawati, Fauna; Kirtishanti, Aguslina (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2024)
Prostate cancer is the second most prevalent cancer in men with approximately 1.4 million men worldwide. The main therapy for prostate cancer is androgen deprivation therapy (ADT), but patients who have received ADT may experience a condition of castration resistant prostate cancer (CRPC). More than 84% of patients have metastasized when diagnosed with CRPC (mCRPC) and median survival about 36 months. The Food & Drugs Association (FDA) has approved a new therapy for mCRPC patients, an example is olaparib. The purpose of this systematic review and meta analysis is to assess effectiveness (overall survival) and safety of olaparib in mCRPC. This research is using randomized control trial’s (RCT) article. The literature search process was carried out using the PubMed database. The quality of inclusion was assessed using the Critical Appraisal Skill Program (CASP) checklist and journal reputation. The results of the meta-analysis on the effectiveness of olaparib has showed that there was no significant difference in the patient's overall survival rate (RR=0. 81; 95% CI=0.58-1.13). The results of the meta analysis on the safety level of olaparib has showed a significant difference, seen from the side effects such as anemia (RR=3.47; 95% CI=2.59-4.65), nausea (RR=2.05; 95% CI=1.62-2.60) and fatigue (RR=1.32; 95% CI=1.10-1.59). The conclusion is olaparib as mCRPC therapy does not show significant effectiveness in improving overall survival in mCRPC. In addition, the low safety level of olaparib in mCRPC patients were seen from side effects such as anemia, nausea and fatigue